2012
DOI: 10.1037/a0027107
|View full text |Cite
|
Sign up to set email alerts
|

Adverse experiences and suicidal ideation in adolescence: Exploring the link using the LONGSCAN samples.

Abstract: Objective Although widely studied in adults, the link between lifetime adversities and suicidal ideation in youth is poorly understood. The purpose of this study was to explore this link in adolescents. Methods The analyses used a sample of 740 16-year-old youth in the LONGSCAN sample, and distinguished between childhood (before the age of 12) and adolescent (between age 12 and age 16) adversities. Results There was a significant link between cumulative lifetime adversities and suicidal ideation. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
(94 reference statements)
2
41
2
4
Order By: Relevance
“…The adversities examined included (1) sexual abuse and molestation (sexual abuse without sexual contact); physical abuse and maltreatment; child abuse and neglect not otherwise specified; (2) family dysfunction and exposure to domestic violence; (3) separation from or death of a biological parent, family member or close friend; parental divorce; (4) poor interpersonal relationships and breaking up with boyfriend/girlfriend; (5) victimization/distress at school. Based on the main findings from our selected studies, experience of adversities or negative life events was significantly related to youth suicidal behavior [17][18][19][20][21][22][23][24]. Another important finding was that some adversities are very common, as is the distress associated with experiencing multiple adversities [18,24].…”
Section: Summary Of Main Findingsmentioning
confidence: 91%
See 3 more Smart Citations
“…The adversities examined included (1) sexual abuse and molestation (sexual abuse without sexual contact); physical abuse and maltreatment; child abuse and neglect not otherwise specified; (2) family dysfunction and exposure to domestic violence; (3) separation from or death of a biological parent, family member or close friend; parental divorce; (4) poor interpersonal relationships and breaking up with boyfriend/girlfriend; (5) victimization/distress at school. Based on the main findings from our selected studies, experience of adversities or negative life events was significantly related to youth suicidal behavior [17][18][19][20][21][22][23][24]. Another important finding was that some adversities are very common, as is the distress associated with experiencing multiple adversities [18,24].…”
Section: Summary Of Main Findingsmentioning
confidence: 91%
“…For example, Thompson et al [23] confirmed that the number of lifetime adversities was associated with adolescent suicidal behavior, but also showed that the impact of adversities early in life could vary depending on whether they occurred during childhood or adolescence. Psychological maltreatment and sexual abuse had a lower impact if they occurred in childhood, and a higher impact if they were experienced in adolescence.…”
Section: Studies On the Association Between The Number Of Adverse Lifmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, Thompson et al (2012) examined the impact of exposure to multiple types of violence at different developmental periods on a critical mental health outcome: suicidal ideation. This study utilized the LONGSCAN data set, which tracked over 1300 youths from ages 4 to 16.…”
Section: Articles In the Special Issuementioning
confidence: 99%